Balarila ng wikang pambansa - Santos, Lope K.; Philippines. Komisyon sa Wikang Filipino (San Miguel, Maynila Komisyon sa Wikang Filipino, 2019)
On grammar of Tagalog language as a national language of the Philippines
Includes bibliographical references (pages xxxix-xli)
Keywords: Language policy -- Philippines; Tagalog language -- Grammar